THE LEGAL IMPLICATIONS OF PERSONAL DATA PROTECTION FOR ELECTRONIC CONTRACTS FROM THE PERSPECTIVE OF INDONESIAN CIVIL LAW - Gunawan Widjaja (Adisam Publisher, 2026)
The rapid growth of electronic transactions in Indonesia has made the protection of personal data a central issue in civil law, particularly regarding the validity and enforcement of electronic contracts. This study aims to analyse the legal implications of personal data protection on electronic contracts from the perspective of Indonesian civil law, focusing on how Law No. 27 of 2022 on Personal Data Protection (PDP Law) affects the validity requirements of contracts and the civil liabilities of the parties. The research method employed is normative legal research using a literature review approach, analysing primary legal sources such as the Civil Code, the ITE Law, and the PDP Law, as well as relevant secondary and tertiary legal materials. The research findings indicate that the PPDL has brought about a fundamental transformation in the legal framework of electronic contracts, wherein the consent of data subjects must meet the standards of informed consent—being explicit, specific, informative, and voluntary—to ensure that the element of agreement under Article 1320 of the Civil Code is materially fulfilled. Violations of personal data protection provisions may be classified as breach of contract or unlawful acts giving rise to civil liability in the form of damages, with a reversal of the burden of proof mechanism that places the data subject in a stronger position. It is concluded that the harmonisation between the Civil Code, the ITE Law, and the PDP Law has created a more comprehensive civil legal ecosystem, although the effectiveness of its enforcement still requires the strengthening of digital legal literacy and consistency in court jurisprudence.